Pre- and in-season body mass changes for Division I collegiate men's basketball athletes considering playing time and years of experience - Beljic, A.; Lockie, R. (The Journal of Strength and Conditioning Research, 2021)
Success in sport is relative to several fitness components, including strength, power, agility, and endurance. Body mass, specifically maintenance of favorable body composition, is directly related to these qualities. A collegiate basketball season can be a strenuous time for the athlete not only because of the high demands of the games and additional stressors (e.g., academic demands), but the relatively short time available to maintain positive physiological adaptations gained in the summer via resistance training. The stress of the season and college in general could reduce performance and negatively affect body composition. Purpose: The purpose of this study was to track body mass changes in Division I collegiate athletes during pre- and in-season and examine which factors may influence changes in this area. Methods: Sixteen NCAA Division I collegiate men's basketball athletes completed a weekly weigh-in for the duration of the 2019-2020 season. Body masses were taken using a high precision medical grade scale each Monday before the players participated in any team activity. All players participated in normal training programs as assigned by the sport and strength and conditioning staff. However, freshmen players had an additional 2 weight room sessions in-season (3-5, as opposed to 1-3 per week), and a senior starter (>30 minutes per game) increased his weight room sessions to 6 sessions a week in-season. A t-test and a repeated measures ANOVA, respectively, as well as descriptive statistics were used to investigate any trends in body mass changes by 2 Methods: grouping the athletes according to minutes played (over or under 10 minutes played per game); and collegiate experience (freshmen to seniors). Results: No significant differences were noted across playing time (p = 0.864) or years of experience (p = 0.093). Players playing a total of 10 minutes or more gained ~0.97 kg body mass, while those that played less gained ~1.76 kg. However, when grouping players by years of experience, the freshman group (6 players) gained ~4.09 kg per player over the pre- and in-season. Although not significant, this was notably different than the senior (1.03 kg per player), junior (-3.63 kg per player) and sophomore (-0.91 kg per player) groups. When analyzing individual body mass differences, the senior starter who lifted 6 times a week gained a total of 4.09 kg. Conclusions: The data suggested that additional weight room sessions may have contributed to additional body mass gains from pre- to in-season, specifically for the freshman and the one senior. Although not statistically significant, this has practical relevance. Additional resistance training prescription could be beneficial for increasing body mass and contributing to the physical development of younger players, especially those not receiving great playing time. This may be especially useful to those teams whose athletes typically stay for all 4 years of college. Practical Application: If body mass is an issue, coaches should identify those players and prescribe additional weight room sessions as soon as possible. Additionally, players who are able to preserve body mass also have the ability to preserve lean muscle tissue, whose preservation is crucial because of the limited resistance training time spent in-season. This could ensure players maintain the muscle mass necessary for high-end performance, and potentially reduce injury risk due to muscle loss later in the season.